Application of a hyperspectral camera for colorimetric measurements on polychrome surfaces in a controlled environment and evaluation of three image processing software for displaying colorimetric data: Pros and cons of the methodology presented. Issue 2 (27th December 2022) - Cherubini, Filippo; Casini, Andrea; Cucci, Costanza; Picollo, Marcello; Stefani, Lorenzo
Abstract: This work explores the potential of a compact hyperspectral camera, Specim IQ, for the remote colorimetric study of polychrome surfaces in controlled environments. These measurements are generally made with dedicated instruments, such as colorimeters or spectrophotometers, which require contact with the surface and coverage areas of the order of 10s of mm 2 . These two characteristics, contact and a very small analysis area, can severely limit the study of polychrome surfaces, since the measured areas are not necessarily representative of the entire surface. In addition, it is not always possible to touch the objects being analyzed. A possible alternative is the use of compact hyperspectral cameras, such as Specim IQ, for the in situ study of the spectral and colorimetric characteristics of these surfaces. To better address this research, which is still in the preliminary phase, a 2 × 45°/0° geometry measuringement was used. The illumination of the image plane at 45° with respect to the camera made it possible to eliminate the components reflected specularly on the camera lens. With this shooting geometry, Labsphere Color and Gray Reflectance Standards (eight color and four gray standards) were analyzed and placed on seven different color backgrounds. With the spectral data acquired, it was possible to calculate the color of the targets and display the colorimetric values by means of three commonly used image processing software packages. In this way, it was possible to define for this hyperspectral camera a measurement‐data processing procedure applicable to measurements in the laboratory aimed at studying the color of polychrome surfaces. Abstract :